Práticas restaurativas no cárcere feminino: instrumento potente para ressignificar a autoimagem da mulher encarcerada e seus laços de pertencimento? - Lima, Raphaela Maria Nascimento (2024)
The research hypothesizes that female imprisonment results in more destructive psychological and social outcomes than male imprisonment, given that women often play a unifying role in their family units, in addition to the issue involving pregnant and breastfeeding incarcerated women. The invisibility around the specificities (biological, physical, and psychological) of women, despite the rising curve of female incarceration in Brazil, especially in the last two decades, is strongly related to the paradigm of patriarchy, which focuses on erasing the female figure. The research takes as a second hypothesis that the restorative logic, by betting on the strengthening of relationships, based on the commitment to the family and social bond, presents tools to redefine the self-image of the imprisoned woman and assist in her return to social coexistence. Therefore, the objective is to verify the power of restorative practices in the female prison environment to reduce negative reflections on the self-image and stigma of the incarcerated woman and, thus, create strategies for strengthening their family and social belonging ties. The methodological path included bibliographic research, as well as analysis of data provided by DEPEN and documentary research of data collected at PREFEM in Sergipe. In addition, with the aim of establishing a possible connection between theory and practice, projects that use restorative practices in female prisons were sought and among those identified, a greater consolidation of these practices was observed in the Piauí State. Therefore, some data were also collected at the Piauí State Court of Justice. Thus, using the method in question, it was concluded at the end of the work that although it is possible to identify a latent potential of restorative practices for the strengthening of women who are behind prison walls and their belonging ties, there is a lack of deepening research in this aspect, especially with the female prison population.